Household perception and recycling behaviour on electronic waste management : a case study of Kuala-Lumpur, Malaysia - Rafia, Afroz; Akhtar, Rulia; Mehedi Masud, Muhammad (Universiti Malaya, 2014)
Electronic waste (e-waste) is increasing rapidly in Malaysia to the effect that e-waste management has now become a major environmental concern in Malaysia, especially Kuala Lumpur. In a step towards remedying this problem, this study seeks to ascertain household awareness, knowledge and risk perception of e-waste and its impact on attitudes and recycling behaviours in Kuala Lumpur. The result shows that three factors, namely, awareness, knowledge and risk perception of e-waste management have positive and significant influence on attitudes towards e-waste mangement. Furthermore, attitudes towards e-waste mangement has a positive influence on recycling behavior. This study provides valuable insights to policy makers so that they may take appropriate steps to increase recycling behaviour among households in Kuala Lumpur.